School Timetabling--A Case in Large Binary Integer Linear Programming - Tripathy, Arabinda (Management science, 1984)
A timetabling problem is formulated as a large integer linear programming problem in 0-1 variables. A solution method based on Lagrangean relaxation coupled with subgradient optimization is presented. The solution method also incorporates a branch and bound procedure which takes advantage of special ordered sets of variables. We present computational results for a large timetabling problem involving 900 subjects in a one-year graduate program.